Research progress in the protection mechanism of omentin-1 in diabetic nephropathy - Liu Yangchun, He Yicao, Zhou Dashun, Zhang Haisong (Xin yixue, 2024)
Diabetic nephropathy is one of microvascular complications of diabetic nephropathy （DN） and the main cause of end-stage renal disease. Inflammation， oxidative stress， endothelial and podocyte dysfunction and metabolic abnormalities play critical roles in the pathogenesis of DN. Increasing evidence has demonstrated that omentin-1 exerts a variety of biological effects and can play a role in kidney protection. In DN patients， omentin-1 levels are generally reduced， which impairs anti-inflammation， anti-oxidative stress， endothelial cell and podocyte function and insulin resistance， and further aggravates the progression of nephropathy. In this article， the protection mechanism of omentin-1 in DN was illustrated from its role in the regulation of inflammation， oxidative stress， improvement of endothelial cell and podocyte function， and improvement of insulin resistance， aiming to provide novel ideas for the diagnosis and treatment of DN.